An Overview on ELT Course Book - Ismit Karim (Jurnal Langua, 2020)
In the practice of teaching and learning, planned teaching material undoubtedly holds a very crucial role. A textbook is the example of the teaching material that has been used for five decades as the manual instruction as well as a source of information in the teaching and learning activity. Merriam-Webster dictionary defines a textbook as "a book about a particular subject that is used in the study of that subject especially in the school". Furthermore, regarding its importance the textbook provides the sources related to the skills, behavioural aspects, believes and knowledge covered by cognitive elements and teaching techniques supported by the curriculum. This article is written as a review on an English course book to find the cultural content presented in that book. Adopting content analysis, this review concludes that the course book offers cultural contents that allow the students to learn certain target culture in term of literature. Some minor drawbacks are highlighted as discussed in this paper.